Identification of yeasts Isolated from processed and frozen cocoa (Theobroma cacao) pulp for wine production - Trindade,Rita de Cássia (1999)
The alternative use of cocoa (Theobroma cacao) for wine production was tested. The pulp samples, obtained from Formosa farm, Itacaré, Brazil, were diluted, homogenized and inoculated on Sabouraud dextrose agar medium (SDA) and incubated at 28º C for 5-8 days. Selected colonies were tested for the ability to ferment cocoa pulp and divided into fermentative, non-fermentative and weak/late fermentative species. Isolates characterized as fermentative were further tested in a small-scale wine production plant and identified. Species from the genus Brettanomyces constituted the main fermentative yeasts, with the exception of two Kloeckera apis samples. The final wine product was normally pale or clear, making clarification unnecessary, and with a sweet or dry pleasant flavor. The predominance of Brettanomyces species in cocoa pulp indicated its ecological importance in this environment and pointed to an active role of Brettanomyces in the deterioration process of the processed cocoa pulp.